Treatment of Cervical Pregnancy with Ultrasound-Guided Intragestational Injection of Methotrexate: A Case Report - Angeliki Rouvali; Panagiotis Vlastarakos; Sofoklis Stavros; Maria Giourga; Kalliopi Pappa; Angeliki Gerede; Alexandros Rodolakis; Ekaterini Domali (Case Reports in Obstetrics and Gynecology)
This study is aimed at describing a noninvasive conservative strategy to the treatment of cervical pregnancy and highlighting the success of ultrasound-guided therapeutic techniques. A 43-year-old woman with a history of one previous cesarean section presented in our unit with vaginal spotting and a positive urine pregnancy test. She was diagnosed with a cervical pregnancy, and she was successfully treated conservatively with the administration of intragestational sac methotrexate under ultrasound guidance. Cervical pregnancy is a rare form of ectopic pregnancy that results from conceptus implantation in the cervical canal. The main concern is the associated life-threatening hemorrhage and subsequent need for urgent hysterectomy. The evolution of ultrasound over the past decades has enabled early diagnosis and has shifted the management from a radical surgical approach towards a stepwise conservative therapeutic approach, when possible.